2014
DOI: 10.3109/19396368.2014.918675
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of oligozoospermia: an oxidative stress perspective

Abstract: Infertile patients presenting with poor semen concentration, motility, and morphology have significantly higher levels of reactive oxygen species (ROS). In this cross-sectional study, our goal was to: 1) determine how semen parameters such as concentration, motility, morphology, as well as ROS are altered in oligozoospermic men alone and those in combination with poor sperm concentration, motility, morphology, and compare these with three control groups; unproven donors, donors with proven fertility <2 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 27 publications
7
64
0
6
Order By: Relevance
“…Reactive oxygen species (ROS) have been extensively studied, and their detrimental effects on male fertility are well accepted. It has already been reported that pathological ROS levels have a deleterious effect on semen quality, including spermatozoa motility [3][4][5], viability, morphology and concentration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) have been extensively studied, and their detrimental effects on male fertility are well accepted. It has already been reported that pathological ROS levels have a deleterious effect on semen quality, including spermatozoa motility [3][4][5], viability, morphology and concentration [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…• Supplementation of 60 mg/day of coenzyme Q10 for 103 days led to an increase in the fertilization rate but had no effect on motility, morphology or concentration in 17 patients with low fertilization rates due to male factor infertility [177] • 60 patients with idiopathic asthenozoospermia who received 200 mg/day of coenzyme Q10 demonstrated significant improvement in motility after 6 months of treatment [178] [11,12]. Nevertheless, significant set up costs have to be taken into consideration, and the data generated by chemiluminescence must be interpreted carefully because a variety of factors can affect the signals obtained [181].…”
Section: Methods For Detecting Reactive Oxygen Speciesmentioning
confidence: 99%
“…Because high levels of ROS have been associated with a decreased male infertility, measuring ROS levels in semen is an important part of the initial evaluation as well as follow-up of men with reproductive dysfunction [10][11][12]. Chemiluminescence and flow cytometry are currently the most common techniques in clinical andrology to assess and study seminal OS.…”
Section: Methods For Detecting Reactive Oxygen Speciesmentioning
confidence: 99%
See 2 more Smart Citations